A colorimetric chemosensor for the sequential detection of copper(II) and cysteine. (May 2015) - Lee, Seul Ah; Lee, Jae Jun; Shin, Jong Won; Min, Kil Sik; Kim, Cheal
Abstract: A simple and easy-to-make colorimetric chemosensor1 for the sequential detection of Cu 2+ and cysteine was developed by combination of hydroxynaphthalene-2-carbaldehyde and diaminomaleonitrile. This sensor1 exhibited an obvious color change from pale yellow to orange in the presence of Cu 2+ in aqueous solution. Also, the resulting1 -Cu 2+ complex sensed cysteine through naked-eye, showing recovery from1 -Cu 2+ to1, over other sulfur-containing amino acid and peptide. Moreover, the sensing ability of1 for Cu 2+ was supported by theoretical calculations. Graphical abstract: Highlights: A simple and easy-to-make colorimetric sensor was synthesized. This sensor could sequentially detect Cu 2+ and cysteine through naked-eye in aqueous solution. The sensing mechanism for Cu 2+ was supported by theoretical calculations.